Study protocol for comparing the efficacy of left-open single-flap technique versus double-flap technique after proximal gastrectomy: A multicenter randomized controlled trial - Yang, Qin Chuan; Wang, Wei Dong; Mo, Zhen Chang; Yue, Chao; Zhou, Hai Kun; Gao, Rui Qi; Yu, Juan; Dong, Dan Hong; Liu, Jin Qiang; Wei, Jiang Peng; Yang, Xi Sheng; Ji, Gang; et al. (Frontiers in Oncology, 2022)
Background Proximal gastrectomy has gradually gained more attention due to its superiority in retaining the function of part of the stomach. The inevitable loss of the antireflux barrier and postoperative complications resulting from proximal gastrectomy can severely affect the quality of life. Continuous improvements in digestive tract reconstruction after proximal gastrectomy have yielded the development of a variety of methods with antireflux functions. Recently, our center attempted the left-open single-flap technique and initiated a multicenter, prospective, randomized controlled trial for patients undergoing proximal gastrectomy to reduce the difficulty of surgical anastomosis and the incidence of perioperative complications compared with the double-flap technique. These findings will provide more evidence-based medical research for the development of clinical guidelines. Methods/design This study is a prospective, multicenter, randomized controlled clinical trial. We plan to recruit 250 patients who are eligible for proximal gastrectomy. After informed consent is obtained, patients will be randomly assigned to the trial group (left-open single-flap technique) and the control group (double-flap technique) in a 1:1 allocation ratio. Discussion Increasingly, clinical studies have focused on the improvement of reconstruction modalities after proximal gastrectomy. Among these methods, the double-flap technique is a clinically effective method. The purpose of this study is to establish a prospective randomized controlled trial to compare the efficacy of the left-open single-flap technique versus the double-flap technique after proximal gastrectomy, aiming to provide more evidence-based medical studies for digestive tract reconstruction in proximal gastrectomy. Clinical Trial Registration ClinicalTrials.gov, identifier [NCT05418920].